A study of the effect of age and gender upon student business ethics - Ruegger, Durwood (Journal of business ethics, 1992)
The present survey was voluntarily and anonymously completed by 2,196 students enrolled in business courses at the University of Southern Mississippi. The intent of the survey was to determine whether or not age or gender played a role in a person's perception of proper ethical conduct., The findings suggests that gender is a significant factor in the determination of ethical conduct and that females are more ethical than males in their perception of business ethical situations., Students were divided into groups according to age as follows: under 21 years, 22–30 years, 31–40 years, and 40 plus years. The results of this survey also suggest that age is a determining factor in making ethical decisions. The statistics suggest that those students falling in the 40 plus years age group were the most ethical, followed in order by the 31–40 group, the 22–30 group and those of 21 years of age and under.